Evaluation of Post-Processing Kinematic (PPK) Accuracy in Urban Area in Turgutlu, Manisa, Türkiye - Pirti, Atinc; Yucel, Mehmet Ali (AGH UNIV SCIENCE & TECHNOLOGY PRESS, 2025)
In recent years, global navigation satellite systems (GNSSs) have emerged as a prominent technology for geolocation applications and services in urban set-tings. Urban environments should also be classified under difficult situations. Densely populated metropolitan areas such as urban centers obstruct the re-ceipt of GNSS signals; these obstacles often result in the congestion of line-of-sight (LOS) signals and give rise to the receipt of diffracted or reflected echoes (often known as the multipath phenomenon). PPK (post-processing kinemat-ic) is a GNSS data-processing method that achieves high-accuracy positioning by correcting errors in raw positioning data. Post-processing is widely used in applications that require precise geospatial information, such as surveying, mapping, and UAV operations. This research aims to evaluate the accuracy of the PPK application method in urban areas. For this aim, surveys were carried out in Turgutlu's province of Manisa on July 15, 2020, in T & uuml;rkiye. The anal-ysis compared the PPK surveys' results with those that were obtained from static surveys. PPK is very effective in difficult situations, but we were likely to encounter certain accuracy problems. Nevertheless, it is worth noting that achieving urban surveys with an accuracy from +/- 1 cm to +/- 2 cm may not always be feasible due to the challenging circumstances that might result in more-significant inaccuracies from +/- 10 cm to +/- 100 cm for both the horizontal and vertical components.
Keywords: static; post-processing kinematic (PPK); urban areas; precision; accuracy; GPS; Engineering; Physical Geography